THE RELATIONSHIP OF SELF-MOTIVATION AND FAMILY SUPPORT AMONG SELF-IMAGES ON POST-STROKE PATIENTS IN POLYCLINIC PHYSIOTHERAPY PMI HOSPITAL BOGOR: HUBUNGAN MOTIVASI DIRI DAN DUKUNGAN KELUARGA DENGAN CITRA DIRI PADA PASIEN PASCA STROKE DI POLIKLINIK FISIOTERAPI RS PMI BOGOR - Widia Widia Astuti (Jurnal Ilmiah Wijaya, 2019)
World Health Organization (WHO) in 2008 describes stroke is included in the seven lists of deadly diseases in the world, The number of people with stroke in Indonesia on 2013 based on the diagnosis of health workers (Nakes) is estimated as many as 1,236,825 people (7.0%). Recorded in August 2016 as many as 116 post-stroke patients undergoing therapy at policlinic physiotherapy RS PMI Kota Bogor. To find out the corelation between self-motivation and family support with self-image on patient who post-stroke at policlinic physiotherapy of RS PMI Kota Bogor in 2017. The type of this research is descriptive quantitative with cross sectional approach. The population of this research is the patient who have post stroke at policlinic physiotherapy of RS PMI Bogor. The sampling technique used was accidental sampling with the number of samples of 90 people, the data analysis technique using chi square test. The result of the research showed that respondents with moderate motivation were 64 (71,1%) respondents, respondents with family support supporting as many as 52 (57,8%) respondents. The result of statistical test obtained p value 0,015 from self motivation variable with self image and p value 0,004 from family support variable with self image (p <0,05). The conclusion of this research is the relationship between self-motivation and family support with self-image on patient who post-stroke at policlinic physiotherapy of RS PMI Kota Bogor in 2017. This research are usefull to improve health education in giving the patient who post stroke and family about the importance of having motivation, Support from families for patients who post-stroke to have a positive impact on the recovery process.